2007
DOI: 10.1242/jcs.03361
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide promotes endothelial cell survival signaling through S-nitrosylation and activation of dynamin-2

Abstract: Endothelial cell-based angiogenesis requires activation of survival signals that generate resistance to external apoptotic stimuli, such as tumor necrosis factor-alpha (TNF-α), during pathobiologic settings. Mechanisms by which this is achieved are not fully defined. Here, we use a model in which the multifunctional cytokine nitric oxide counterbalances TNF-α-induced apoptosis, to define a role for membrane trafficking in the process of endothelial cell survival signaling. By perturbing dynamin GTPase function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
102
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(110 citation statements)
references
References 42 publications
5
102
0
Order By: Relevance
“…Of course eNOS contributes to angiogenic EC signaling, 8,22 however, previous work from us and others has also demonstrated that NO limits hepatic stellate cell migration, motility, and other features of activation that lead pericytes toward a myofibroblast phenotype. 3,7 These observations led us to hypothesize that NO may have beneficial effects on tumor progression by attenuating the tumor-progressing effects of myofibroblasts and the matrix derived from these cells.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Of course eNOS contributes to angiogenic EC signaling, 8,22 however, previous work from us and others has also demonstrated that NO limits hepatic stellate cell migration, motility, and other features of activation that lead pericytes toward a myofibroblast phenotype. 3,7 These observations led us to hypothesize that NO may have beneficial effects on tumor progression by attenuating the tumor-progressing effects of myofibroblasts and the matrix derived from these cells.…”
Section: Discussionmentioning
confidence: 92%
“…The retroviral transduction system resulted in nearly 100% transfection efficiency as we have previously described. 22 As Ϫ/Ϫ mice with myofibroblast markers such as NG2, SMA, and desmin showed positivity for the three markers. Although some co-localization was noticed between some markers many of the cells displayed only one of the markers.…”
Section: Nent (Figure 2b) Staining For Enos Revealed No Detection Inmentioning
confidence: 90%
“…This is specially supported by the up-regulation of dynamin-2, already known as a survival factor for bovine endothelial cells (Kang-Decker et al, 2007). Conversely, the transcription activator ets variant gene 5, involved in cell growth and differentiation, was down-regulated, but even so the augmented expression of this gene is associated with several mouse cardiomyopathies (Spurney et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…30 Previous studies have demonstrated that NO can stimulate endocytosis by S-nytrosilation of dynamin. 31,32 Therefore, we tested whether dynamin-mediated endocytosis was involved in NO-induced ILK degradation by using a specific inhibitor of dynamin activity, Dyngo 4a. Confocal microscopy showed that dynamin was mediating the NO-dependent internalization of ILK into endosomes.…”
Section: No Triggers Ilk Endocytosis Through a Dynamin-dependent Pathwaymentioning
confidence: 99%